Integration of Science and Qur'anic Education: A Solution to Heal Inner Wounds in the Modern Era. - Muti’ah Nuha Mumtazah (Spiritus: Religious Studies and Education Journal, 2025)
This study aims to examine the urgency of integrating science and Qur'anic education as a solution to heal the spiritual wounds of modern society. Through a qualitative approach and literature review of several relevant journals, this research demonstrates that the integration of science and Qur'anic education not only addresses the identity crisis faced by the youth but also enhances the spiritual and intellectual development of students. Educational models that combine Islamic values and scientific knowledge, such as STEAM-based Islamic education, tafsir kauniyah, and Qur'anic logotherapy, have been proven to strengthen students' motivation, reduce psychological stress, and deepen their understanding of the world and life as creations of Allah. This study also recommends expanding this integration at various educational levels and supporting it with relevant policies. Future research should further explore the long-term impact of implementing Qur'anic-scientific education on the quality of life and character development of the younger generation.